2014
DOI: 10.2113/econgeo.110.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Variations Within Podiform Chromitite Deposits in the Shetland Ophiolite: Implications for Petrogenesis and PGE Concentration

Abstract: The Shetland ophiolite, located to the northeast of the Scottish mainland, contains podiform chromitites. Two of these are known to host extremely anomalous PGE concentrations. The chromitite at Cliff is enriched in Pt, Pd, and Rh PGE (PPGE) and the Harold's Grave chromitite is enriched in Ir, Ru, and Os PGE (IPGE). Analysis of multiple samples of chromitite from chromite quarry spoil tips and surrounding chromite-bearing dunite and chromite-bearing harzburgite has revealed that there are links between the chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…The highest Co, Mn, Zn, Fe and lowest Ga were mainly recorded in strongly altered small chromite occurrences from the Rhodope massif in Bulgaria. They are in a good agreement with other chromitites [21][22][23][24][25] and are independent of the age of the associated ophiolites. Platinum-group elements (PGE) show total contents ranging from 30 to 6120 ppb and Pd/Ir ratios from 0.06 to 34, which are independent of the major element composition of chromitites ( Table 2).…”
Section: Distribution Of Trace Elements In Chromititessupporting
confidence: 81%
See 1 more Smart Citation
“…The highest Co, Mn, Zn, Fe and lowest Ga were mainly recorded in strongly altered small chromite occurrences from the Rhodope massif in Bulgaria. They are in a good agreement with other chromitites [21][22][23][24][25] and are independent of the age of the associated ophiolites. Platinum-group elements (PGE) show total contents ranging from 30 to 6120 ppb and Pd/Ir ratios from 0.06 to 34, which are independent of the major element composition of chromitites ( Table 2).…”
Section: Distribution Of Trace Elements In Chromititessupporting
confidence: 81%
“…A tectonic discrimination of peridotites, using the oxygen fugacity (f O 2 )-Cr#[Cr/(Cr + Al)] diagram, and the Ga-Ti-Fe 3+ # [Fe 3+ /(Fe 3+ + Cr + Al)] systematics in chrome-spinels, has been proposed [16]. A negative correlation between Ga and Cr in chromitites has been established, that may be related to the composition of parental magmas [17][18][19][20][21][22][23][24] or to the outer electronic structure of Ga that is similar to that of Al [25]. Also, the investigation of spinels in lithospheric mantle xenoliths from distinct tectonic settings has demonstrated that trace elements contribute in discriminating between spinels hosted in peridotites and those crystallized from magmas [11].…”
Section: Introductionmentioning
confidence: 99%
“…1), have particularly anomalously high ug/g values of PGEs: The Cliff locality is extremely enriched in Pt, Pd and Rh compared with ophiolitic chromitites worldwide; whereas, in contrast, he Harold's Grave local y s IPGE e r ched (Table 1), both containing total PGE concentrations in excess of 60 ug/g (Prichard and Lord, 1993). The PGE concentrations in the ophiolite and the history of their discovery are summarised in Brough et al (2015). Detailed petrogenetic studies of the various chromitite pods within the Baltasound area highlight significant short-range variability in chemical and Os isotopic characteristics, implying derivation for a source with short-range heterogeneity feeding magmas through a series of distinct co d s (O'Dr scoll e al , 2012; Derbysh re e al , 2013).…”
Section: Platinum-group Elements In the Shetland Ophiolitementioning
confidence: 99%
“…Thus, it appears that at least some of the PGEs may have been distributed according to local fractional crystallisation processes, which led to the differentiation of peridotites, norites and orthopyroxenites in the Fiskefjord region. Unfortunately, currently no PGE data is available for the chromitite layers hosted by the Seqi dunites, but it is not unlikely that these could also host PGE mineralisation (e.g., [30,65,69,20]. Interestingly, the dunites all have Pd contents below the detection limit, which may thus be concentrated elsewhere in the magmatic system perhaps as a result of sulfide saturation (cf., [74].…”
Section: Platinum-group Element Patternsmentioning
confidence: 99%